Studies on 4 - dimethylaminopyridinium salicylate monohydrate's optical, mechanical, and laser damage threshold. (August 2021) - Arun kumar, A.; Rathika, A.; Subramaniyan, R. Raja; Subash Chandra Bose, R.; Balasubramanian, K.
Abstract: Slow evaporation solution growth was used to grow single crystals of 4-dimethylaminopyridinium salicylate monohydrate. Single crystals of good optical quality with dimensions up to 14 × 6 x5 mm 3 are obtained. Single crystal X-ray diffraction analysis verified the unit cell parameters of the grown crystals. In the wavelength range of 200–1100 nm, the UV–Vis–NIR Transmittance spectrum was observed. Vicker's microhardness test was used to examine the mechanical behaviour of the grown crystal. Using 5 ns laser pulses at a 10 Hz repetition rate from a Q-switched Nd: YAG laser with a wavelength of 1064 nm, the laser damage threshold value was calculated. Highlights: DMAPSA has a positive solubility gradient in the methanol-water (1:1) solvent. DMAPSA crystal has a transparency window in the range 265–1100 nm and possess an optical band gap (Eg ) of 4.6 eV. The threshold value for single shot laser damage is 7.286 J/cm 2 at 1064 nm laser radiation.